Telaah Efektivitas Bahan Ajar Bahasa Arab Berbasis Pendidikan Karakter - Susiawati; Bachtiar, Fauziah; Kudus, Ruhul; Jamal, Mardhiana; Lailaa, Hikmatul (CV. SINAR HOWUHOWU, 2026)
Character education is a priority in the Indonesian education system and can be integrated into Arabic language learning, including in non-formal education. Arabic language teaching materials based on character education have the potential not only to improve language skills but also to instill positive character values in students. This study aims to analyze the effectiveness of character education-based Arabic language teaching materials implemented at the Majelis Taklim Al Mubarok Tamalanrea Indah Makassar. This study used a qualitative approach with content analysis techniques supported by quantitative data from pre- and post-tests. Data collection was conducted through documentation, observation, interviews, and tahsin and translation ability tests involving 14 participants. The results showed a significant increase in tahsin ability, from an average of 69.57 to 85.50 (a 22.9% increase), and translation ability, from 73.43 to 87.92 (a 19.7% increase). The main difficulties faced by participants included pronouncing the letter Ra (100%), the word Allah (92.9%), and the letter Dod (85.7%). These findings indicate that Arabic language teaching materials integrated with character education are effective in improving students' cognitive and affective aspects in the context of learning in the majelis taklim (Islamic study groups).